Eating disorder symptoms and foraging for food related items - Árni Kristjánsson; Auður Helgadóttir; Tómas Kristjánsson (Journal of Eating Disorders, 2021)
Abstract Background Foraging tasks have recently been increasingly used to investigate visual attention. Visual attention can be biased when certain stimuli capture our attention, especially threatening or anxiety-provoking stimuli, but such effects have not been addressed in foraging studies. Methods We measured potential attentional bias associated with eating disorder symptoms to food related stimuli with our previously developed iPad foraging task. Forty-four participants performed a foraging task where they were instructed to tap predesignated food related targets (healthy and unhealthy) and other non-food objects and completed four self-report questionnaires measuring symptoms of eating disorders. Participants were split into two groups based on their questionnaire scores, a symptom group and no symptom group. Results The foraging results suggest that there are differences between the groups on switch costs and target selection times (intertarget times) but they were only statistically significant when extreme-group analyses (EGA) were used. There were also notable food versus non-food category effects in the foraging patterns. Conclusions The results suggest that foraging tasks of this sort can be used to assess attentional biases and we also speculate that they may eventually be used to treat them through attention bias modification. Additionally, the category effects that we see between food items and other items are highly interesting and encouraging. At the same time, task sensitivity will need to be improved. Finally, future tests of clinical samples could provide a clearer picture of the effects of eating disorder symptoms on foraging for food.